Teacher’s Strategies in Teaching Speaking to Young Learners - Pratama, Erik Yuda; Awaliyah, Yani (ENGLISH JOURNAL, 2016)
The proficiency of speaking becomes one of the five skills that should be acquired by every child in this 21 century era (Seamolec on line course 2: 2006). Communicating and collaborating and language boundaries become a necessity in diverse and multinational communities. Mutually beneficial relationships are a central undercurrent to accomplishment in Business (Partnership for 21st century skills: 2008). This research is aimed to investigate the teacher’s strategies, problems and solutions for teaching speaking to young learners. A case study design was used in this study, and the data were collected through observation, interview, and written document. The data from these three instruments were analyzed qualitatively. This research has found several strategies promoted by the lecturer when teaching speaking to young learners. In the classroom activities, the lecturer used several strategies such as, role play, watching videos, jazz chant, digital storytelling, games, and repetition. The teachers might face several barriers in the classroom such as reluctant students, missing pronunciation and lack of vocabularies. But he can overcome those barriers by using various techniques of teaching speaking to young learners, such as implementing media and designing the lesson using topical-based syllabus (Pinter, 2006).